Money, credit and banking - Aleksander Berentsen; Gabriele Camera; Christopher Jude Waller (Center for Economic Studies and ifo Institute (CESifo), 2005)
In monetary models in which agents are subject to trading shocks there is typically an ex-post inefficiency in that some agents are holding idle balances while others are cash constrained. This inefficiency creates a role for financial intermediaries, such as banks, who accept nominal deposits and make nominal loans. We show that in general financial intermediation improves the allocation and that the gains in welfare arise from paying interest on deposits and not from relaxing borrowers? liquidity constraints. We also demonstrate that increasing the rate of inflation can be welfare improving when credit rationing occurs.
Keywords: D9; E5; E4; 330; money; credit; rationing; banking; Geldtheorie; Geld; Kredit; Mengenrationierung; Geldmengensteuerung